Pengaruh Tekanan Karyawan dan Tekanan Pemegang Saham terhadap Sustainability Reporting - Anna, Yane Devi; Salsabilla, Adinda Khairunisa; Aulia, Andini Putri; Mala, Dinda; Wulandari, Nani (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
This study aims to analyze the influence of employee pressure and shareholder pressure on sustainability reporting. The background of this research is based on the increasing demand for transparency in non-financial reporting that encompasses environmental, social, and governance (ESG) aspects amid growing global awareness of sustainability issues. This study employs a quantitative approach with causal associative research design. The population consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Sustainability reporting is measured based on the Global Reporting Initiative (GRI) Standards indicators, while employee pressure is measured using the natural logarithm of the number of employees, and shareholder pressure is measured through the proportion of shares held by institutional investors.